Bolu Kukus Ubi Ungu sebagai Inovasi MPASI: Langkah Awal dalam Program Pencegahan Stunting di Kelurahan Jakatan Raya - Rivaldi Putra Pradana; Misnawati Misnawati; Wingga Pratama; Ayu Saputri; Rusiana Rusiana; Albert Gregori; Hafifah Putri; Rahmat Rahmat; Rolan Rolan; Nur Hanadia Rahman; Mika Rosalina; Patrick Aines Simanihuruk; Dea Minahtri Anggreni; Shelvina Shelvina (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Stunting is a chronic nutritional problem that has a significant impact on children's physical and cognitive growth. In Jakatan Raya Village, Rungan District, Gunung Mas Regency, the stunting rate is still high, mainly due to the lack of balanced nutritional intake in early life. This article discusses community service aimed at introducing purple sweet potato steamed cake as an innovation for Complementary Breast Milk (MPASI) to prevent stunting. This activity includes training, mentoring, and evaluation of the effectiveness of purple sweet potato steamed cake in increasing children's nutritional intake. The results showed an increase in mothers' knowledge about the importance of MPASI, positive acceptance of this innovation, and an increase in nutritional intake in children. Although effective, challenges related to access to raw materials and variations in presentation still need to be overcome for the sustainability of the program.